2014
DOI: 10.1177/1078155214551315
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy may contribute to an increased risk for metabolic syndrome in patients with breast cancer

Abstract: Adjuvant chemotherapy may contribute to an increased risk for metabolic syndrome in patients with BC and these changes are more profound in pre-menopausal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…To the best of our knowledge, the current study is the largest study to date to systematically address the effect of (neo)adjuvant chemotherapy alone on MetS and its components in both premenopausal and postmenopausal women. Smaller studies have reported MetS or its components after the completion of all treatments for breast cancer …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the current study is the largest study to date to systematically address the effect of (neo)adjuvant chemotherapy alone on MetS and its components in both premenopausal and postmenopausal women. Smaller studies have reported MetS or its components after the completion of all treatments for breast cancer …”
Section: Discussionmentioning
confidence: 99%
“…Obese, diabetic breast cancer patients undergoing chemotherapy have increased likelihood of side effects including infection and chemotherapy-related toxicity (Srokowski, et al 2009). In addition, cytotoxic therapy has been associated with treatment-related weight gain and metabolic syndrome in breast cancer patients (Bicakli, et al 2014; Makari-Judson, et al 2014), potentially exacerbating these aforementioned side effects. In prostate cancer, obesity is associated with weight gain and increased risk of diabetes following androgen deprivation therapy (Keto, et al 2011; Tsai, et al 2014), particularly among older men (Morgans, et al 2014).…”
Section: Non-biologic Mechanisms Contributing To the Obesity - Canmentioning
confidence: 99%
“…Therefore, anthracycline may cause long-term atherosclerosis and cardiotoxicity through thrombocyte reactivation when evaluated with present preclinic studies. Also, metabolic syndrome parameters related to atherosclerosis were previously shown to get worse in the breast cancer patients receiving adjuvant anthracycline [32]. When our study is evaluated with previous studies, we have suggested that anthracyclines may cause long-term cardiotoxicity by provoking atherosclerosis.…”
Section: Discussionmentioning
confidence: 58%